Analysis in Honoring the Power of Thought Using Soag Game (Senang Otak Atik Gambar) - Anita Afrianingsih; Dina Amalia; Yushinta Eka Farida (Indonesian Journal of Early Childhood Education Studies, 2023)
The purpose of the research to be carried out is to analyze the Android-based SOAG learning media, the planning process for making SOAG learning media and the use of SOAG media to hone children's thinking power. The research subjects were children aged 5-6 years of PAUD Toddies School, with a population sampling technique through non-probability sampling a total of 27 students. So that the sample is taken from the entire population. Data collection techniques from the implementation of this study used observation, interviews and documentation. The data analysis used is qualitative data analysis by referring to the concept of Miles and Huberman with an emphasis on data reduction, data presentation and drawing conclusions. The result of this research is that the process of implementing the SOAG game (Senang Otak Atik Gambar) can be carried out from planning, learning practice and evaluation. In the planning stage, the teacher must make the RPPH more attractive. The learning practice stage uses the SOAG game (Senang Otak Atik Gambar), at this stage the teacher is able to convey the material in more detail, using different teaching styles and methods than usual. As the teacher explains with a visual learning style. The evaluation stage of the SOAG game (Senang Otak Atik Gambar) uses observations and interviews given to children and teachers in providing assessments. This evaluation is an important tool for teachers to determine the level of success of children in improving their cognitive abilities through the SOAG game (Senang Otak Atik Gambar). The conclusion of this study is that the SOAG game learning media (Senang Otak Atik Gambar) is very appropriate and effective to use to optimally hone children's high-level thinking power.